The Implementation of Kit Built Concept Mapping to Help Non-English Department Students Improve their Reading Skills - Asri, Atiqah Nurul; Andoko, Banni Satria (IJET (Indonesian Journal of English Teaching), 2019)
Reading skill is important especially for non-English departments students like those of Information Technology Department at State Polytechnic of Malang. However, based on the observation and the results of the tests, the students showed low performance and motivation in reading English written texts even though the texts were on IT related subjects. Therefore, the students were introduced to Kit-Built Concept Mapping to help them overcome the problems. This study is Classroom Action Research (CAR) to analyze the implementation of the method to help the students improve their reading skills as well as motivation to read. There were some procedures they had to follow and some tests to do in this study. This study was said to be successful and stopped when the students’ scores met the criteria of success previously determined, namely more than 50% of them had the average score more than 66 or B in accordance with the State Polytechnic of Malang Academic Handbook. After the first and second cycles, the average scores obtained showed an improvement both in the first and second cycles. Hence, after the two average scores were analyzed by the paired t-test it was found that there was no significant difference between them. Accordingly, it can be said that this method was not fully successful in improving the students' reading skills even though from the questionnaire and interview showed the students’ interests and motivation to read English written texts more than before.